2021
DOI: 10.1016/j.amjoto.2020.102779
|View full text |Cite
|
Sign up to set email alerts
|

Emergency videoendoscopic endonasal tracheal intubation for severe upper airway stenosis

Abstract: Purpose Upper airway stenosis is one of the most formidable situations in medicine and is frequently encountered in the ENT clinic. We introduce here our method of emergency endonasal endotracheal intubation under videoendoscopic observation. Methods Transnasal endoscopic observation was done, and the region of airway stenosis was detected. Then, the endotracheal tube was prepared and the endoscope was inserted into the tube. The endoscope with tube was inserted up to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…A preoperative flexible nasoendoscopy with tongue protrusion has also been shown to improve the prediction of the modified Cormack–Lehane grade during a conventional laryngoscopy [ 31 ]. A prospective feasibility study and a case series report showed that a fiberoptic nasal endoscope armed with an intubating tube could be used for the awake nasotracheal intubation of a cohort with upper airway pathology, revealing the possibility of using this device for both airway evaluation and management in elective cases or emergencies [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A preoperative flexible nasoendoscopy with tongue protrusion has also been shown to improve the prediction of the modified Cormack–Lehane grade during a conventional laryngoscopy [ 31 ]. A prospective feasibility study and a case series report showed that a fiberoptic nasal endoscope armed with an intubating tube could be used for the awake nasotracheal intubation of a cohort with upper airway pathology, revealing the possibility of using this device for both airway evaluation and management in elective cases or emergencies [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three cases accompanied by a deep throat and pharyngeal abscess required surgical drainage. These cases underwent tracheostomy, so the tube was extubated [12].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, flexible scope intubation allows maintenance of spontaneous negative-pressure ventilation for a patient in whom airway collapse or obstruction may occur with muscle paralysis and positive-pressure ventilation, as may be the case for a patient with Ludwig's angina. Furthermore, flexible scope intubation is now seen as the preferred first-line approach to securing the airway for these patients, supplanting the previous gold standard technique, a surgical airway [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%